Home in the Poetry of Saudi Distinguished Poets: Abdullah Al-Faisal a Case in Point (3): Home in the Poetry of Saudi Distinguished Poets - Dahami, Yahya (Hasanuddin University, 2024)
The diversity of poetry, the gifts of literature, the elegance of language, and the inventiveness of poets are manifestations of the homeland. It is common knowledge that a large amount of poetry has been sacrificed for the homeland and that a great number of Saudi poets have written and are composing golden letters in honor of their homeland, the Kingdom of Saudi Arabia. It is the homeland, the everlasting love, and it constantly will be the homeland, regardless of how forcefully the poet demands it. The final section of this three-part paper seeks to demonstrate Abdullah Al-Faisal's competence, knowledge, and proficiency through one of his poems while also highlighting his allegiance to the vast country to which he belongs. After briefly discussing poetry and its value, the study examines the Kingdom of Saudi Arabia: Poetry and the concept of Homeland before reviewing the words of the poet Abdullah Al-Faisal's career. This study is primarily focused on the poem